Characterization of TLR1 and expression profiling of TLR signaling pathway related genes in response to Aeromonas hydrophila challenge in hybrid yellow catfish (Pelteobagrus fulvidraco ♀ × P. vachelli ♂) - Guo, Shengtao; Gao, Wenxue; Zeng, Mengsha; Liu, Fenglin; Yang, Qingzhuoma; Chen, Lei; Wang, Zesong; Jin, Yanjun; Xiang, Peng; Chen, Hanxi; Wen, Zhengyong; Shi, Qiong; et al. (Frontiers in Immunology, 2023)
Toll-like receptor 1 (TLR1) mediates the innate immune response to a variety of microbes through recognizing cell wall components (such as bacterial lipoproteins) in mammals. However, the detailed molecular mechanism of TLR1 involved in pathogen immunity in the representative hybrid yellow catfish (Pelteobagrus fulvidraco ♀ × P. vachelli ♂) has not been well studied. In the present study, we identified the TLR1 gene from the hybrid yellow catfish, and further comparative synteny data from multiple species confirmed that the TLR1 gene is highly conserved in teleosts. Phylogenetic analysis revealed distinguishable TLR1s in diverse taxa, suggesting consistency in the evolution of the TLR1 proteins among various species. Structural prediction indicated that the three-dimensional structures of TLR1 proteins are relatively conserved among different taxa. Positive selection analysis showed that purifying selection dominated the evolutionary process of TLR1s and the TLR1-TIR domain in both vertebrates and invertebrates. Expression pattern analysis based on the tissue distribution showed that TLR1 is mainly transcribed in the gonad, gallbladder, and kidney, and the mRNA levels of TLR1 in the kidney were remarkably up-regulated after Aeromonas hydrophila stimulation, indicating that TLR1 participates in the inflammatory responses to exogenous pathogen infection in hybrid yellow catfish. Homologous sequence alignment and chromosomal location indicated that the TLR signaling pathway is very conserved in the hybrid yellow catfish. The expression patterns of TLR signaling pathway-related genes (TLR1 and TLR2, MyD88, FADD, and caspase 8), were consistent after pathogen stimulation, revealing that the TLR signaling pathway is triggered and activated after A. hydrophila infection. Our findings will lay a solid foundation for better understanding the immune roles of TLR1 in teleosts as well as provide basic data for developing strategies to control disease outbreaks in hybrid yellow catfish.